On the impact of product quality attributes on open source project evolution - Silva, A. C. B. G. da. (2022)
Several Open Source Software (OSS) projects have adopted frequent releases as a strategy to deliver both new features and fixed bugs on time. This cycle begins with express requests from the project’s community, registered as issues in bug repositories by active users and developers. Each OSS project has its own priorities established by their respective communities. A a still open question is the set of criteria and priorities that influence the decisions of which issues should be analyzed, implemented/solved and delivered in next releases. In this paper, we present an exploratory study whose goal is to investigate the influence of target product quality attributes in software evolution practices of OSS projects. The goal is to search for evidence of relationships between these target attributes, priorities assigned to the registered issues and the ways they are delivered by product releases. To this end, we asked six participants of an exploratory study to identify these attributes through the data analysis of repositories of three well-known OSS projects: Libre Office, Eclipse and Mozilla Firefox. Evidence indicated by the participants suggest that OSS community developers use criteria/priorities driven by specific software product quality attributes, to plan and integrate software releases.